Oya (Goddess of Whirlwind) - Balogun, Lekan (Literamed Publications Nigeria Ltd, 2008)
Oya is a historical play that gives a vivid account of the historic fight between ogun, the Yoruba god of iron and Sango, the Yoruba god of thunder, over who wins the favour of the beauty, Oya.
Keywords: Drama; Nigeria(English)